Reproduction of Halicarcinus planatus (crustacea, decapoda, hymenosomatidae) in the Deseado River estuary, southwestern Atlantic Ocean - Vinuesa, Julio Hector; Ferrari, Lucrecia (Marine Biology)
The small spider crab Halicarcinus planatus, is a common resident in the rocky coasts of the Magellanic region in South America. The H. planatus population in the Deseado River estuary differs from other populations of the same species in the spatial segregation of sexes. Between March 2002 and October 2003, samples were taken monthly from the lower intertidal and upper subtidal levels. All crabs captured were females. Additional samplings were carried out at the subtidal level to search for the presence of males. A total of 3346 females were captured and their relative age was determined. Some of these females were maintained in the laboratory to study the terminal moult and the spawning seasons. The analysis of the ovary development of adolescents (ADO) and mature (MAT) females, and the times when females of different ages appear, when spermatophores are found inside spermathecae, and when post-spawning mortality takes place allowed us to establish the whole reproductive process. Adolescents are impregnated only once before the terminal moult. There are 7 or 8 spawnings after the moult, with a brief resting period between two successive reproductive seasons. The life span of mature females ranges between 15 and 22 months. Results indicate that the H planatus population of the Deseado river estuary differs greatly from that of the Kerguelen Islands. Fil: Vinuesa, Julio Hector. Universidad Nacional de la Patagonia "San Juan Bosco". Facultad de Humanidades y Ciencias Sociales - Sede Comodoro. Centro de Desarrollo Costero; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Ferrari, Lucrecia. Universidad Nacional de Luján; Argentina